Centering the document — Towards a critical studio pedagogy in graphic design (Journal of Applied Learning and Teaching, 2021)
As a designer and educator, I endeavor for this article to make an intervention in the way that graphic design is imagined, taught, discussed/debated, and practiced. I believe that graphic design objects mediate forms of sociality in ways that are banal and largely underexamined. This article explores the implications of an historiography that narrates the entanglement of graphic design with the administration of the settlerstate and capitalist enterprise through the genre of the document. Broadly defined, the document serves as the substrate for archival ways of knowing that are imposed as a function of the ideological hegemony of statist governance and corporate bureaucracy. As an instrument of state and capital, the document circumscribes how the world is named, and impacts the way it is ordered. Recognizing this is a prerequisite for mounting a challenge to this condition. This assertion is meant to serve as the backdrop against which to speculate on a different kind of graphic design pedagogy, charged with the education of practitioners who imagine and create other forms of what the radical pedagogue Paulo Freire (author of Pedagogy of the Oppressed) calls “naming the world.” The intent of this article is to initiate an exploration of a framework for graphic design pedagogy charged with cultivating a student’s capacity to experiment with and invent forms that might actualize critical and emancipatory modes of sociality.